The Potential of UTHM Pagoh Campus as a Tourism Site - Mohd Zamran, Muhammad Norzahin; Mohamad, Salasiah (Enhanced Knowledge in Sciences and Technology, 2023)
Ecotourism is a form of sustainable tourism that focuses on preserving natural environments and promoting the well-being of local communities. It involves visiting natural areas, such as forests, wetlands, and wildlife reserves, for the purpose of education, research, and enjoyment. Ecotourism activities can include hiking, wildlife viewing, bird watching, and cultural tours. This study aims to provide evidence that UTHM possesses the attributes necessary to become a thriving ecotourism destination. It has the potential to become better known in the local community and more well-known overall through the practice of eco-tourism. This research aims to highlight and promote UTHM Pagoh as one of the campus ecotourism destinations in Malaysia. It also hopes to reveal the potential of several attractions that could be found in-campus and in the surrounding vicinity. These attractions could be helpful to be developed and packaged as eco-tourism products. UTHM Pagoh Campus in Muar, Johor, will serve as the focus of this research. This is due to its moderate size and the fact that it is situated in a village environment where tourists would have the opportunity to visit the natural locations. The culmination of this endeavor is the fabrication of memento prototypes that reflect the local culture. Site visits, scan observations, and field sampling were utilized to obtain information. The selected places included the UTHM campus in Pagoh, the Educational Hub in Pagoh, the Nasuha Herbs & Spice Farm, and the Ayer Hitam Utara Forest Reserve. Tomb of Sultan Alauddin Riayat Shah I and Masjid Lama Kampung Olak Sepam, Pagoh are presented as prospective items derived from this research. In the near future, tourism packages must be tested before to being released and promoted on the market. This report identifies and discusses numerous other attractions and prospective products uncovered through this investigation.